Intralesional margin after excision of a high‐grade osteosarcoma: Is it a catastrophe?. Issue 4 (18th May 2022) - Tsagkozis, Panagiotis; Gaston, Czar L.; Styring, Emelie; Haglund, Felix; Grimer, Robert
Abstract: Background and Objectives: Treatment of high‐grade osteosarcoma (OS) relies on a combination of systemic chemotherapy and radical surgical excision of the tumor. Little is known on what happens in case of an irrefutably inadequate (intralesional) margin. We aimed to describe the outcome of patients with high‐grade OSs of the trunk and the extremities where planned wide resection resulted in an intralesional margin. Methods: A retrospective study from the Scandinavian Sarcoma Group registry and the Royal Orthopaedic Hospital databases including data from 53 patients surgically treated between the years 1990 and 2017. Results: Local recurrence was observed in 13/53 patients. All patients with local recurrence where the neoadjuvant chemotherapy response could be retrieved ( n  = 9) were shown to be poor responders. None of the patients with good response to chemotherapy relapsed. Postoperative radiotherapy was not associated with improved local control of the disease. Re‐excision surgery was performed in only seven patients, and two of them had tumor relapse. Conclusions: Good response to chemotherapy salvages the outcome of surgical excision with a poor margin in patients with high‐grade OSs and a watchful waiting strategy may be justified in these cases. Poor responders have a higher recurrence risk and their approach should be individualized.